2001
DOI: 10.1103/physrevd.64.025011
|View full text |Cite
|
Sign up to set email alerts
|

Manifest covariance and the Hamiltonian approach to mass gap in (2+1)-dimensional Yang-Mills theory

Abstract: In earlier work we have given a Hamiltonian analysis of Yang-Mills theory in (2+1) dimensions showing how a mass gap could arise. In this paper, generalizing and covariantizing from the mass term in the Hamiltonian analysis, we obtain two manifestly covariant and gauge-invariant mass terms which can be used in a resummation of standard perturbation theory to study properties of the mass gap.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…An elegant prescription for doing that was proposed in [3]. In this section we provide a brief review of the analytic continuation suggested in [3].…”
Section: Minkowski Continuationmentioning
confidence: 99%
See 4 more Smart Citations
“…An elegant prescription for doing that was proposed in [3]. In this section we provide a brief review of the analytic continuation suggested in [3].…”
Section: Minkowski Continuationmentioning
confidence: 99%
“…A construction that is very reminiscent of fuzzy spheres was carried out in [3] to regulate the integrals over the Lorentz group. One constructs states with a fixed value of Q which we denote by M − 1.…”
Section: Minkowski Continuationmentioning
confidence: 99%
See 3 more Smart Citations